2022
DOI: 10.3390/d14020076
|View full text |Cite
|
Sign up to set email alerts
|

ITS DNA Barcoding Reveals That Halophila stipulacea Still Remains the Only Non-Indigenous Seagrass of the Mediterranean Sea

Abstract: Non-indigenous species (NIS) are one of the major threats to the native marine ecosystems of the Mediterranean Sea. Halophila stipulacea was the only exotic seagrass of the Mediterranean until 2018, when small patches of a species morphologically identified as Halophila decipiens were reported in Greece. Given the absence of reproductive structures during the identification and the taxonomic ambiguities known to lead to misidentifications on this genus, we reassessed the identity of this new exotic record usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…On the other hand, one characteristic example of a macroalgal species which was revised in the current inventory is Halophila decipiens. The seagrass H. decipiens was reported with a single population in Salamina, Greece in 2018 [97] but its identification was based only on vegetative morphological characters; a subsequent study employing DNA barcoding demonstrated that the Greek population actually corresponds to a morphologically variant H. stipulacea [98], hence H. decipiens was removed from the Greek national inventory and consequently from the Mediterranean baseline. Despite ongoing progress in elucidating the identity and origin of many macroalgal cryptic species [99], there is a clear need for more molecular and phylogeographic studies of this species group.…”
Section: Species Validation and Uncertaintiesmentioning
confidence: 99%
“…On the other hand, one characteristic example of a macroalgal species which was revised in the current inventory is Halophila decipiens. The seagrass H. decipiens was reported with a single population in Salamina, Greece in 2018 [97] but its identification was based only on vegetative morphological characters; a subsequent study employing DNA barcoding demonstrated that the Greek population actually corresponds to a morphologically variant H. stipulacea [98], hence H. decipiens was removed from the Greek national inventory and consequently from the Mediterranean baseline. Despite ongoing progress in elucidating the identity and origin of many macroalgal cryptic species [99], there is a clear need for more molecular and phylogeographic studies of this species group.…”
Section: Species Validation and Uncertaintiesmentioning
confidence: 99%
“…In Cannes harbor (NW Mediterranean Sea), H. stipulacea was probably introduced via big yachting coming by Suez Canal and are establishing stable population which could indicate that conditions are now more favorable for long-term population establishment (Thibaut et al, 2022). H. stipulacea is presently the only non-native seagrass in the Mediterranean Sea (Garcıá-Escudero et al, 2022). It generally colonizes habitats devoid of native seagrass, forms mixed meadows with C. nodosa (Winters et al, 2020), or colonizes dead matte of P. oceanica (Thibaut et al, 2022).…”
Section: Shifts In the Export Of Seagrass Detritusmentioning
confidence: 99%